Radiation resistance of Ti—20Zr alloy in microcrystalline and nanocrystalline state - Belous, V.A.; Borodin, O.V.; Bryk, V.V.; Vasilenko, R.L.; Voyevodin, V.N.; Kuprin, A.S.; Ovcharenko, V.D.; Reshetnyak, E.N.; Tolmachova, G.N. (Functional Materials, 2013)
In this work we studied structure of Ti—20Zr alloy in recrystallized and nanocrystalline conditions before and after irradiation by Zr³⁺ ions with energy 1.8 MeV to 80 dpa at 500° C. By transmission electron microscopy methods it was showed that irradiation of the alloy in the recrystallized state induced formation of c type dislocation loops, which are common characteristic of accelerated radiation-growth of the materials with hcp lattice. Irradiation of the nanostructured material leads to an isotropic increase in the grain size (from 49 nm to 146 nm); the signs of accelerated radiation-growth were not detected.